Hydrogel from acellular porcine adipose tissue promotes survival of adipose tissue transplantation. (30th April 2021) - Liu, Peng-Cheng; Tan, Qiu-Wen; Zhang, Yi; Wang, Hua; Zhou, Li; Yang, Qian-Ru; Xu, Li; He, Tao; Xie, Hui-Qi; Lv, Qing
Abstract: Lipofilling is a popular technique for soft tissue augmentation, limited by unpredictable graft survival. This study aimed at exploring the effect of hydrogel from acellular porcine adipose tissue (HAPA) on angiogenesis and survival of adipose tissue used for lipofilling. The effect of HAPA on adipose-derived stem cells (ADSCs) proliferation, adipogenic differentiation, and vascular endothelial growth factor (VEGF) secretion were evaluated in hypoxia and normoxia in vitro . For the in vivo study, adipose tissue with phosphate buffered saline, ADSCs, and HAPA (with or without ADSCs) were co-injected subcutaneously into nude mice. HAPA–ADSCs mixture (tissue engineering adipose tissue) was also grafted. Gross observation, volume measurement, and ultrasound observation were assessed. For histological assessment, hematoxylin and eosin, perilipin, cluster of differentiation 31 (CD31), Ki67, and transferase-mediated d-UTP nick end labelling (TUNEL) staining were performed. HAPA improved ADSCs proliferation, VEGF secretion, and adipogenic differentiation under normoxia and hypoxia conditions in vitro study. For the in vivo study, HAPA showed improved volume retention and angiogenesis, and reduced cell apoptosis when compared to ADSCs-assisted lipofilling and pure lipofilling. In conclusion, HAPA could maintain ADSCs viability and improve cell resistant to hypoxia and might be a promising biomaterial to assist lipofilling.